Measuring the Effectiveness of a Hybrid Pedagogy in a Large-Scale Community College Soft Skills Intervention. Issue 4 (3rd April 2023) - Almonte, Richard; McAfee, Heather; Snell, Ted; Ahmed, Ahsan
ABSTRACT: In 2013, an urban college developed a mandatory soft skills course. Unique among postsecondary institutions, the course has been running since fall 2015. Research has now been conducted into the effectiveness of the course. A mixed-methods research study collected primary data and a literature review of the pertinent secondary data. Data sets include a comparison of co-op employer ratings of students in a semester before the course was mandated and a semester after the course was mandated; a survey of co-op employers to rate their co-op student's soft skills achievement; and a pre-post/post-pre survey of current students asking them to rate the importance of soft skills, their knowledge and demonstration of soft skills, and their intention to use soft skills. All data strongly support the claim that the course has been a positive soft skills intervention. Hypotheses are shown to be valid: current students see the course as an effective way of improving their understanding of soft skills, their ability to deploy soft skills, and their intention to deploy soft skills in future; and, co-op employers see it as a positive intervention by reporting more effective demonstration of soft skills among co-op students who have taken the course than among co-op students from other institutions who have not taken the course. We conclude that offering a course that follows our pedagogy is the most effective way to increase postsecondary student soft skills capabilities and ensure employers continue to be satisfied with graduate soft skills.